The Effectiveness of the Implementation of Operational Standards for Maternal and Child Health Services in Improving the Quality of Maternity Services at RSIA Rosiva - Dewi Agustina; Wuni Barokah; Pane, Jihan Mawaddah; Saragih, Nazla Novrinda; Mendriani, Putri (Sean Institute, 2025)
This study aims to evaluate the application of Standard Operating Procedures (SOP) in maternal and child health services, especially maternity services at RSIA Rosiva. Quality health services are one of the important aspects in ensuring patient safety and satisfaction, especially for mothers who are about to give birth. The method used in this study is a descriptive qualitative method with data collection techniques through in-depth interviews and direct observation in the field. The results of the study show that administratively, SOPs have been prepared and socialized to health workers, but in practice there are still several obstacles. These obstacles include delays in medical treatment, a fairly convoluted administrative process, and a lack of coordination between service units. This shows that even though the SOP already exists, its implementation has not been fully effective and consistent. In addition, the satisfaction of maternity patients with the services provided is still not optimal, as can be seen from complaints related to waiting time and lack of information provided by medical personnel. This study concludes that improving the quality of services can be done by strengthening the implementation of SOPs, improving the competence of health workers through training, and improving the administrative system to be more responsive to patient needs. The results of this study are expected to be input for hospital management in efforts to continuously improve the quality of maternity health services.